Incidence and transplacental transmission of Neospora caninum in primiparous females from Bos indicus slaughtered in Presidente Pradente, São Paulo, Brazil - Vianna, Luis Carlos [UNESP]; Sartor, Izidoro Francisco [UNESP]; Pituco, Edviges Maristela.; Okuda, Liria Hiromi; Camargo, Clarice Neves; Kronka, Sergio do Nascimento (Universidade Estadual de Londrina (UEL), 2008)
To produce an epidemiological map of neosporosis in Brazil and identify the types of transmission of this disease, the present study evaluated the occurrence of Neospora caninum in Nelore cattle (Bos indicus) in Presidente Prudent, west region of São Paulo state; its vertical transmission; and the early stage in which fetuses are infected. To achieve this, serum samples from 518 slaughtered pregnant heifers and their fetuses were tested by ELISA technique and fetal brain tissues subjected to PCR. One hundred and three heifers (19.88%) had antibodies to N. caninum, as well as 38 (36.8%) of fetuses from 4 months of gestation. The conventional PCR failed to detect N. caninum DNA. These findings show that neosporosis occurs in the area studied and that it may be transmitted the transplacental route, althought N. caninum had not detected in brain tissue from non-aborted fetuses. The use of nested PCR it would be applied to increase the sensitivy of test.
Keywords: epidemiology; cattle; Neospora caninum